2020
DOI: 10.3390/s20195608
|View full text |Cite
|
Sign up to set email alerts
|

RDCPF: A Redundancy-Based Duty-Cycling Pipelined-Forwarding MAC for Linear Sensor Networks

Abstract: Existing duty-cycling and pipelined-forwarding (DCPF) protocols applied in battery-powered wireless sensor networks can significantly alleviate the sleep latency issue and save the energy of networks. However, when a DCPF protocol applies to a linear sensor network (LSN), it lacks the ability to handle the bottleneck issue called the energy-hole problem, which is mainly manifested due to the excessive energy consumption of nodes near the sink node. Without overcoming this issue, the lifespan of the network cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In [19], Zhang et al presented the Redundancy DCPF (RDCPF) protocol. This proposal incorporates redundant nodes to reduce the traffic bottlenecks and the excessive energy consumption experienced by nodes located near the sink.…”
Section: A Mac Protocols For Lsn'smentioning
confidence: 99%
“…In [19], Zhang et al presented the Redundancy DCPF (RDCPF) protocol. This proposal incorporates redundant nodes to reduce the traffic bottlenecks and the excessive energy consumption experienced by nodes located near the sink.…”
Section: A Mac Protocols For Lsn'smentioning
confidence: 99%
“…The authors of [16] identified that DCPF networks may suffer from an energy-hole problem, where nodes near the sink node consume an excessive amount of energy. To address this problem, they propose the redundancy-based DCPF (RDCPF) protocol, which involves the deployment of redundant nodes in a LWSN.…”
Section: Related Workmentioning
confidence: 99%
“…In [20,21], the authors analyze strictly linear WSNs, i.e., networks that consist of a single line of nodes (whereas in [13][14][15][16][17][18][19] the LWSN is assumed to be dense). The authors propose a routing algorithm that uses implicit acknowledgments to provide reliability and connectivity with energy efficiency, low latency, and fault tolerance.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the purpose of using wireless sensors in factories is to monitor the production environment for ensuring safe production conditions. However, to achieve full coverage of the monitoring in the production workshop, the factory has to place redundant sensors to ensure the performance of the IWSNs, which causes a lot of waste of sensor energy and speeds up the replacement of sensors [9]. In this case, it is necessary to propose a method that can effectively utilize redundant sensors for reducing the number of sensor replacements.…”
Section: Introductionmentioning
confidence: 99%